A cost‐utility analysis comparing CT surveillance, PET‐CT surveillance, and planned postradiation neck dissection for advanced nodal HPV‐positive oropharyngeal cancer. Issue 18 (1st June 2021) - Fu, Terence S.; Scheffler, Patrick; Forner, David; Noel, Christopher W.; Huang, Shao Hui; Gilbert, Ralph W.; Goldstein, David P.; O'Sullivan, Brian; Mehanna, Hisham M.; Waldron, John; de Almeida, John R.
Abstract : Background: The cost utility of image‐guided surveillance using computed tomography (CT) and positron emission tomography (PET)‐CT to planned postradiation neck dissection (PRND) was compared for the management of advanced nodal human papillomavirus‐positive oropharyngeal cancer following chemoradiation. Methods: A universal payer perspective was adopted. A Markov model was designed to simulate four treatment approaches with 3‐month cycles over a lifetime horizon: 1) CT surveillance, 2) standard PET‐CT surveillance, 3) a novel PET‐CT approach with repeat PET at 6 months postchemoradiation for equivocal responders, and 4) PRND. Parameters including probabilities of CT nodal progression/resolution, PET avidity, recurrence, and survival were obtained from the literature. Costs were reported in 2019 Canadian dollars and utilities were expressed in quality‐adjusted life years (QALYs). Deterministic and probabilistic sensitivity analyses were performed to evaluate model uncertainty. Results: PET‐CT surveillance dominated CT surveillance and PRND in the base case scenario, and the novel PET‐CT approach was the most cost‐effective strategy across a wide range of variables tested in one‐way sensitivity analysis. On probabilistic sensitivity analysis, novel PET‐CT surveillance was the most cost‐effective strategy in 78.1% of model iterations at a willingness‐to‐pay of $50, 000/QALYs. Novel PET‐CT surveillance resulted in a 49% lower rate of neck dissection compared with traditional PET‐CT, and yielded an incremental benefit of 0.14 QALYs with average cost savings of $1309. Conclusions: Image‐guided surveillance including PET‐CT and CT are more cost effective than PRND. The novel PET‐CT approach with repeat PET for equivocal responders was the dominant strategy and yielded both higher benefit and lower costs compared with standard PET‐CT surveillance. Abstract : Image‐guided surveillance with positron emission tomography‐computed tomography (PET‐CT) and CT is more cost effective than planned postradiation neck dissection for advanced nodal human papillomavirus‐positive oropharyngeal cancer. A novel PET‐CT surveillance approach involving repeat imaging at 6 months postchemoradiation was the most cost‐effective strategy for managing advanced nodal human papillomavirus‐positive oropharyngeal cancer.